The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep28587
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of EMT-inducing Transcription Factors (EMT-TFs) in Metastatic Breast Cancer: A Systematic Review and Meta-analysis

Abstract: The epithelial-to-mesenchymal transition (EMT) is a vital control point in metastatic breast cancer (MBC). TWIST1, SNAIL1, SLUG, and ZEB1, as key EMT-inducing transcription factors (EMT-TFs), are involved in MBC through different signaling cascades. This updated meta-analysis was conducted to assess the correlation between the expression of EMT-TFs and prognostic value in MBC patients. A total of 3,218 MBC patients from fourteen eligible studies were evaluated. The pooled hazard ratios (HR) for EMT-TFs suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 61 publications
0
69
2
Order By: Relevance
“…The EMT process had been exhibited to play a vital role in cancer metastasis. 35 In this study, by evaluating the expression of major markers of EMT, we observed that knockdown of ZFAS1 greatly decreased the expression of MMP2, MMP9, N-cadherin, Integrin β1, ZEB1, Twist, and Snail, as well as markedly upregulated E-cadherin level, suggesting that ZFAS1 might promote glioma metastasis via inducing EMT.…”
Section: Discussionmentioning
confidence: 70%
“…The EMT process had been exhibited to play a vital role in cancer metastasis. 35 In this study, by evaluating the expression of major markers of EMT, we observed that knockdown of ZFAS1 greatly decreased the expression of MMP2, MMP9, N-cadherin, Integrin β1, ZEB1, Twist, and Snail, as well as markedly upregulated E-cadherin level, suggesting that ZFAS1 might promote glioma metastasis via inducing EMT.…”
Section: Discussionmentioning
confidence: 70%
“…However, the mechanism for LNM in PTC has not been comprehensively reported. EMT is a well-known process involved in cancer metastasis 38,39. There are functional genes modulating EMT, resulting in tumor progression 32.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the aggressive role of LAPTM4B can be achieved by regulating EMT has not been demonstrated. EMT described as a biological process involved in wound healing, cancer progression, metastasis and drug resistance of various human cancers, including BC [3, 5, 27, 28]. The loss of E-cadherin expression and the increase in mesenchymal proteins including Vimentin are considered hallmarks of EMT [3, 29].…”
Section: Discussionmentioning
confidence: 99%